Complete genome sequence of Leuconostoc gelidum subsp. gasicomitatum KG16-1, isolated from vacuum-packaged vegetable sausages - Andreevskaya, Margarita (Stand Genomic Sci, 2016)
Leuconostoc gelidum subsp. gasicomitatum is a predominant lactic acid bacterium (LAB) in spoilage microbial communities of different kinds of modified-atmosphere packaged (MAP) food products. So far, only one genome sequence of a poultry-originating type strain of this bacterium (LMG 18811(T)) has been available. In the current study, we present the completely sequenced and functionally annotated genome of strain KG16-1 isolated from a vegetable-based product. In addition, six other vegetable-associated strains were sequenced to study possible “niche” specificity suggested by recent multilocus sequence typing. The genome of strain KG16-1 consisted of one circular chromosome and three plasmids, which together contained 2,035 CDSs. The chromosome carried at least three prophage regions and one of the plasmids encoded a galactan degradation cluster, which might provide a survival advantage in plant-related environments. The genome comparison with LMG 18811(T) and six other vegetable strains suggests no major differences between the meat- and vegetable-associated strains that would explain their “niche” specificity. Finally, the comparison with the genomes of other leuconostocs highlights the distribution of functionally interesting genes across the L. gelidum strains and the genus Leuconostoc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40793-016-0164-8) contains supplementary material, which is available to authorized users.